2012
DOI: 10.1007/978-3-642-27278-3_28
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Foliar Pigment Concentration of Rice Crop Using Integrated Hyperspectral Index

Abstract: Abstract. Photosynthetic pigment concentration has strong relationship with nitrogen (N) concentration which is an essential element of plant growth and plays an important role in estimating the net primary productivity (NPP) in terrestrial ecosystem research and precision agriculture (PA). In this study, hyperspectral reflectance and pigment concentration of the upper three leaves of rice crop (Oryza sativa L.) with five N fertilization rates were measured in the laboratory. The results showed that there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
2
1
0
Order By: Relevance
“…Our findings revealed that LAI increased up to heading, and thereafter decreased (Table 3). The similar changes in LAI at different growth phases of rice has been reported earlier [12,53,54].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings revealed that LAI increased up to heading, and thereafter decreased (Table 3). The similar changes in LAI at different growth phases of rice has been reported earlier [12,53,54].…”
Section: Discussionsupporting
confidence: 87%
“…Our findings revealed that LAI increased upto heading and thereafter decreased (Table 3). The similar changes in LAI at different growth phases of rice has been reported earlier [54,55].…”
Section: Discussionsupporting
confidence: 86%
“…Moreover, the visible regions of the spectral spaces are useful for estimating the vegetation fraction in multi-crop and background datasets ( Gitelson et al, 2002 ). The LAI was maximum at the booting stage after the subsequent loss in the LAI with each growth step ( Liu et al, 2012 ) due to the loss in photosynthetic activity under the same environmental conditions ( Wu et al, 2016 ). The rice yield was positively correlated with the LAI near the heading, maintaining the larger leaf area duration before heading until harvesting ( Song et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%